Distribuição de barreira dos sistemas 6,7Li + 144Sm em energias próximas à da barreira Coulombiana - Otomar, Denilson Ramos (2009)
Elastic and quasi-elastic excitation functions for the 6,7 Li + 144 Sm systems were measured at backward angles for a range of energies from well below the barrier to above it. Moreover, barrier distributions were extracted from these excitation functions by a point difference method, using the first derivative of the excitation function. The analysis of the data was performed by using the code FRESCO, and the São Paulo potential as a parameter free bare one. From the analysis, on concluded that the inelastic excitations of 144 Sm are extremely relevant for that reactions in the absence o break-up channel. Furthermore, for the Li + 144 Sm reaction the nucleon transfer channel was included in the coupled scheme. An important point that must be taken into account is that, as no parameter of the São Paulo potential was changed, no attempt was made to fit the data, but rather, to compare the experimental excitation function and its corresponding barrier distribution with the theoretical predictions by using a coupling scheme that takes into account the above mentioned inelastic and transfers channels. This comparison for the excitation function gives reasonable good agreement, except at the higher energies. For the barrier distributions, one can notice more clearly that even at the barrier energy there is some disagreement between the experimental results and theoretical calculations. This discrepancy is not unexpected, since as Li are weakly bound projectile, one additional channel should also be included in the coupling scheme: the break-up channel. In order to verify the influence of the break-up channel in the quasi-elastic process, we performed calculations using the CDCC (Continuum Discretized Coupled Channels) method, since the break-up process feeds states in the continuum. In our calculations we assume the clusters model, which means that the Li break-up into deuteron and alpha particles. These clusters interact separately with the target before and after the ocurrence of the break-up. So, by adding this channel into the previously mentioned couple scheme, and excluding the transfer channel from coupling scheme of Li, the comparison the theoretical calculation with the experimental data gives rise to an excellent accuracy in the whole energy range for both the excitation function and the barrier distribution. It is important to mention that there were no fittings parameters in our calculation.